Formal Research In Rauf Parfi's Lyrics – Content Features Of Triangles - Umaraliyеva Nafisa Qurbonali Qizi (Zien Journals, 2025)
Formal innovations in the development of modern Uzbek poetry were studied on the example of poet Rauf Parfi's poetry and his triplets. In the work of the poet, a triptych inspired by hokku in classic Japanese poetry was analyzed. Hokku and triad characteristics were compared. The literary and philosophical characteristics of the three were compared. Similarities and differences of terzina, musallas and hokku, characteristics of Rauf Parfi triplets and Japanese hokku were comparatively studied. The comparative-typological method was used.
Keywords: Hokku; triplet; terzina